2016
DOI: 10.22201/iisue.20072872e.2016.19.185
|View full text |Cite
|
Sign up to set email alerts
|

Estereótipos de género e sexismo em docentes do ensino superior

Abstract: La socialización de género ocurre cotidianamente y marca de forma indeleble la identidad individual, así como la cultura de las organizaciones y de los grupos. La interacción entre discentes e docentes forma parte del proceso de socialización de género. De ese modo, diversas investigaciones muestran que la atención que se presta y las expectativas que los docentes tienen de los alumnos y las alumnas son diferentes. En esta investigación se buscó analizar y caracterizar a un grupo de docentes universitarios por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
1
3
0
6
Order By: Relevance
“…The results showed that sexist attitudes exist to varying degrees in all the countries, which shows that trainee teachers are not free of gender biases and stereotyped beliefs (Carretero & Nolasco, 2019;Cordón et al, 2019). Just as other studies have found that sexism still takes part of the discourses and practices of in-service teachers (Díaz & Anguita, 2017;Sales-Oliveira et al, 2016), research confirms that sexism is also present in future teachers, who will educate the new generations. Additionally, a qualitative study of trainee teachers found that these often encounter difficulties in detecting the existence of covert gender inequalities (Pinedo et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The results showed that sexist attitudes exist to varying degrees in all the countries, which shows that trainee teachers are not free of gender biases and stereotyped beliefs (Carretero & Nolasco, 2019;Cordón et al, 2019). Just as other studies have found that sexism still takes part of the discourses and practices of in-service teachers (Díaz & Anguita, 2017;Sales-Oliveira et al, 2016), research confirms that sexism is also present in future teachers, who will educate the new generations. Additionally, a qualitative study of trainee teachers found that these often encounter difficulties in detecting the existence of covert gender inequalities (Pinedo et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…A study conducted with a sample of future teachers found that levels of hostile sexism were significantly higher in men than in women (Carretero & Nolasco, 2019). Likewise, a study with a sample of in-service teachers showed that women presented fewer hostile attitudes than men (Sales-Oliveira et al, 2016). The results pointed in the same direction.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Nesse sentido se tem o sexismo como "um conjunto de estereótipos sobre a avaliação cognitiva, afetiva e atitudinal acerca do papel apropriado na sociedade, dirigida aos indivíduos de acordo com o sexo" (FORMIGA et al, 2002, p. 105). Os estereótipos são formados por um conjunto de crenças estruturadas sobre as características dos integrantes de um determinado grupo, que causam danos ao promover o preconceito e a discriminação (PLOUS, 2003;SALES-OLIVEIRA;VILLAS-BOAS;LAS-HERAS, 2016).…”
Section: Introductionunclassified